Research on Assisting Clinicians to Operate rTMS Precisely Based on the Coil Magnetic Field Spatial Distribution With Magnetic Resonance Imaging Navigation - Li, Shijun; Wang, Yi; Li, ShengJie; Lv, Yanwei; Zhang, Lei; Zou, Jun; Ma, Lin (Frontiers in Neuroscience, 2019)
OBJECTIVE： To assist clinicians to operate repetitive Transcranial Magnetic Stimulation (rTMS) precisely based on the coil magnetic field spatial distribution with Magnetic Resonance Imaging (MRI) Navigation. METHODS: A fast method for calculating electromagnetic fields in layered brain structures in frequency domain was proposed. By approaching Bessel function in different intervals, the integral with a highly oscillatory kernel was transformed into two parts: a definite integral and a weakened oscillatory one. The distribution of induced current density and magnetic field intensity of rTMS stimulation effect on brain was quantitatively calculated, so that clinicians could intuitively grasp the safe range of coil stimulation on brain. Then, the crucial factor of the stimulation effect of rTMS was determined, and an accurate coil positioning of the rTMS efficiently was completed. Result: The maximal attenuation of induced electric field and magnetic induction intensity was 72.20% and 86.867% at 3 cm away from the skin in the brain layered model. The clinical examination results of electric field intensity distribution, magnetic field intensity distribution, current density distribution, layered brain modeling and coil location speed in the brain model teaching group were significantly higher than those in the traditional teaching group (P < 0.001). CONCLUSION: It is suitable for clinicians to quickly complete the precise positioning of rTMS, master the adjustment of coil stimulation therapeutic parameters, and realize the precise positioning operation of rTMS with MRI navigation in intracranial.